Taxpayers' Legal Awareness Regarding Reporting Changes in Land and Building Tax Objects Via Tax Object Notification Letter in Mojokerto Regency - Sofia Ardini; Eny Sulistyowati (Universitas Negeri Surabaya, 2025)
Changes in Land and Building Tax (PBB) objects are mandatory to be reported via a Tax Object Notification Letter (SPOP) according to Mojokerto Regent Regulation Number 71 of 2020 concerning Procedures for Collecting Regional Taxes. This research aims to analyze the legal awareness of taxpayers regarding reporting changes to Land and Building Tax objects through Tax Object Notification Letters as well as analyzing the obstacles faced by taxpayers in Harmoni Residence Housing, Mojokerto Regency regarding reporting changes to Land and Building Tax objects. This writing is included in empirical legal writing using data collection techniques through interviews and observation. The data analysis technique used in this research is descriptive analytical. The research location is at Harmoni Residence Housing, Mojokerto Regency and the Regional Revenue Agency of Mojokerto Regency. The results of research on taxpayers' legal awareness regarding reporting changes to Land and Building Tax objects through the Tax Object Notification Letter show a low value. Efforts to increase taxpayers' legal awareness in this research are by conducting legal counseling and routine passive and active supervision from the Mojokerto Regency Regional Revenue Agency.